KAJIAN SOSIOLINGUISTIK TERHADAP RAGAM BAHASA DALAM SYAIR SERAT PENJAJAH - Anwarul Mufid; Hasan Arif; Bagus Sinawan Aji; Nurman Alvin Bahris (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the language variety in the Serat Penjajah poem using a sociolinguistic approach, in order to reveal the social, cultural, and ideological meanings contained therein. This poem contains a representation of the suffering of the common people due to oppression and injustice during the Dutch colonial period, which is represented through the use of various variations of the Javanese language, including the ngoko dialect, sociolect, idiolect, and chronolect. The analysis shows that the language variety is not merely a means of communication, but also a reflection of social stratification, cultural identity, and a form of symbolic resistance to the colonial power structure. The sociolinguistic approach shows that language in literary works has an important role as a medium for social criticism and efforts to fight for justice. This finding confirms that traditional literary works, such as the Serat Penjajah poem, function dually as historical sources and as tools of social resistance that are still relevant in the current context.